HUBUNGAN KETERSEDIAAN FASILITAS BENGKEL DENGAN HASIL BELAJAR PADA MATA DIKLAT LAS OKSI-ASETILIN WELDING KELAS XI JURUSAN TEKNIK MESIN DI SMK NEGERI I KOTA JANTHO - Muharir Muharir; Arwizet K; Yufrizal A; Primawati Primawati (Jurnal Vokasi Mekanika (VoMek), 2021)
Basically, Vocational High School (SMK) can also be said to be a school with an outline of learning using practical tools (workshop facilities). This study aims (1) to reveal the relationship between workshop facilities and student learning outcomes in the XI class of the Oxy-acetyline Welding class of Mechanical Engineering Department at SMK Negeri I Jantho City. (2) Describe a description of the learning outcomes of class XI students in the Oxy-Acetilin Welding subject, Mechanical Engineering Department, State Vocational High School I, Jantho City. (3) Defining the effect of workshop facilities on learning outcomes in the subject of welding technique at Oxy-Acetylene Welding class XI SMK Negeri I Jantho City. Types of correlation research. The population in this study amounted to 27 people and all taken as research subjects. The research tool used is in the form of a questionnaire which is arranged in the form of a Liker Scale. Where data collection is obtained from even semeter values ??for the 2020/2021 school year. Of the 40 instrument items tested for the validity of the workshop facility questionnaire, there were 36 valid items. The result of the reliability test was 0.96 which was stated as a reliable instrument. The learning outcomes of the Oksi-Acetylene Welding training course fall into the medium category. Description of data from 27 respondents where the average score obtained was 77.55. While the middle score is 78. In this study, the correlation coefficient of mechanical engineering workshop facilities on the Oksi-Acetilin Welding training course, Mechanical Engineering Department of SMK Negeri I Jantho City is 0.73 and the coefficient of determination is 53.29%. Based on the hypothesis testing, the rcount is 0.73%> 0.381 and the tcount is 5.34> 1.703 at the 5% confidence level. Then the hypothesis Ha is accepted, meaning that there is a relationship between workshop facilities and learning outcomes and Ho is rejected.